Effect of probiotics plus zinc supplementation on clinical outcomes of infants and children with acute infectious diarrhea: a randomized controlled trial - Deldar Morad Abdulah; Saad Jbraeil Sulaiman; Zaid Waad Ahmed (The Korean Pediatric Society, 2024)
Background Findings are conflicting regarding the effect of zinc supplementation on disease severity in children with acute gastroenteritis. Purpose To examine the effects of probiotics and zinc on the clinical outcomes of infants and children with acute infectious diarrhea. Methods In this randomized controlled trial, children with mild or moderate to severe acute gastroenteritis in the Kurdistan Region from November 2021 to June 2022 were diagnosed clinically and randomly assigned to the experimental or control group. The experimental group (n=50) received probiotics and zinc, whereas the control group (n=51) received probiotics alone for 1 week. The product contained live Bifidobacterium infantis, Lactobacillus paracasei, and Lactobacillus rhamnosus (10×106 colony-forming units/day for 7 days). Zinc syrup was administered to the probiotic plus zinc group. Each 5 mL of syrup contained 15 mg of zinc sulfate. Dehydration and disease severity in both groups were measured using the Clinical Dehydration Scale and the Modified Vesikari Scale, respectively. An illness episode was defined as an episode of gastroenteritis with a total score of ≥9 on the Modified Vesikari Scale (range, 0-20). Results The probiotic and probiotic plus zinc groups were similar in age (1.79 years vs. 1.69 years, respectively; P= 0.645), sex (male/female ratio: 1.43 and 1.0, respectively; P=0.373), and medical characteristics. The groups had similar mean dehydration and disease severity scores and a similar incidence of dehydration recovery (some dehydration, 3.92% and 4.00%, respectively; P=1.000), and recovery from mild gastroenteritis (0.0% and 2.0%, respectively; P=0.495) at 2 weeks. Significant decreases in mean dehydration severity and disease severity score (1.80 to 0 and 6.66 to 0, respectively; P<0.001) and the development of dehydration (some dehydration, from 94.0% to 4.0%; P<0.001) from baseline to 2 weeks were noted in the probiotics plus zinc group. The probiotics group responded similarly. The development of mild gastroenteritis was significantly reduced from baseline to 2 weeks (90.2% to 0% and 78.0% to 2.0% in the probiotics and probiotics plus zinc groups, respectively; P<0.0001). The probiotics plus zinc group had a shorter mean recovery time (1.34 days vs. 2.00 days, respectively; P<0.001). Conclusion Taking probiotics plus zinc did not significantly affect disease severity in children with gastroenteritis at 2 weeks. However, the probiotics plus zinc group recovered more quickly than the probiotics group.